SMART DOCS: A New Patient-Centered Outcomes and Coordinated-Care Management Approach for the Future Practice of Sleep Medicine. - Kushida, Clete A; Nichols, Deborah A; Holmes, Tyson H; Miller, Ric; Griffin, Kara; Cardell, Chia-Yu; Hyde, Pamela R; Cohen, Elyse; Manber, Rachel; Walsh, James K (Sleep, 2015)
ABSTRACT: The practice of medicine is currently undergoing a transformation to become more efficient, cost-effective, and patient centered in its delivery of care. The aim of this article is to stimulate discussion within the sleep medicine community in addressing these needs by our approach as well as other approaches to sleep medicine care. The primary goals of the Sustainable Methods, Algorithms, and Research Tools for Delivering Optimal Care Study (SMART DOCS) are: (1) to introduce a new Patient-Centered Outcomes and Coordinated-Care Management (PCCM) approach for the future practice of sleep medicine, and (2) to test the PCCM approach against a Conventional Diagnostic and Treatment Outpatient Medical Care (CONV) approach in a randomized, two-arm, single-center, long-term, comparative effectiveness trial. The PCCM approach is integrated into a novel outpatient care delivery model for patients with sleep disorders that includes the latest technology, allowing providers to obtain more accurate and rapid diagnoses and to make evidence-based treatment recommendations, while simultaneously enabling patients to have access to personalized medical information and reports regarding their diagnosis and treatment so that they can make more informed health care decisions. Additionally, the PCCM approach facilitates better communication between patients, referring primary care physicians, sleep specialists, and allied health professionals so that providers can better assist patients in achieving their preferred outcomes. A total of 1,506 patients 18 y or older will be randomized to either the PCCM or CONV approach and will be followed for at least 1 y with endpoints of improved health care performance, better health, and cost control. CLINICAL TRIALS NUMBER: http://www.clinicaltrials.gov, NCT02037438.